Factors Affecting Residential House Prices in Malaysia - Cheong, Wai Hoong (2010)
This research attempts to examine the factors which have significant influence on house prices in Malaysia. It looks into the dynamics of housing prices from the second quarter of 1999 to the fourth quarter of 2009. Independent variables which have been tested against house price in Malaysia are changes in real Gross Domestic Product, Kuala Lumpur Composite Index, Consumer Price Index, Average Lending Rate, Housing Approval and Outstanding Residential Loan in Commercial Banks. Employing the multi regression analysis, this research shows that changes in house prices could be largely explained by changes in real gross domestic product and changes in Kuala Lumpur Composite Index. A hedonic model for house price is developed from the multiple regression analysis to facilitate the prediction of house prices based on the independent variables. In summary, this research highlights the source and nature of the property price fluctuation in Malaysia and let investors or policy makers to formulate an appropriate strategy to meet their objective in investing or making changes to current policy.